OTHER COMPREHENSIVE INCOME DAN LEVERAGE PADA REAL EARNING MANAGEMENT - Dyah Ayu Retno Inten (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims todetermine the effect of other comprehensive income and leverageon real earnings management in manufacturing companies in thepharmaceutical sub-sector listed on the IDX for the period 2020-2024. This study uses a quantitative method, and the type of data used is secondary data. The population in this study is allmanufacturing companies in the pharmaceutical sub-sector listed on the IDX for the period 2020-2024, totaling 50 samples. Sampling in this study used the purposive sampling technique. The results of the studyconclude that partially, the disclosure of other comprehensiveincome has a significant negativeeffect on real earnings management, while leverage is not significant on realearnings management. Simultaneously, the disclosure of othercomprehensive income and leverage does not have a simultaneous effecton real earnings management. The implication for company managementis that it is expected to increase the transparency of financial reports as a whole andstrengthen the quality of financial reporting to maintain the trust of investors andother stakeholders.